2013
DOI: 10.1180/claymin.2013.048.2.17
|View full text |Cite
|
Sign up to set email alerts
|

Micro-scale experimental investigation of the swelling anisotropy of the Callovo-Oxfordian argillaceous rock

Abstract: International audienceAn experimental study of the swelling anisotropy of the Callovo-Oxfordian argillaceous rock under hydration is presented. The investigation, which combines environmental scanning electron microscopy (ESEM) and digital image correlation techniques, has been carried out at the micrometric scale of the composite microstructure of the rock. Specimens were hydrated in the ESEM over a wide range of relative humidity and observations conducted on two planes: plane 1 parallel to the bedding plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 8 publications
0
25
3
1
Order By: Relevance
“…Although these papers develop elaborate constitutive laws, they provide very limited microstructural observations. The need for micromechanical observations was already recognised by Yang et al (2012) and Wang et al (2013Wang et al ( , 2015. From DIC applied to optical and environmental scanning electron microscope (ESEM) images, these authors showed how heterogeneous strain fields correlate with microstructure and recognised shear bands and tensile microcracks.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although these papers develop elaborate constitutive laws, they provide very limited microstructural observations. The need for micromechanical observations was already recognised by Yang et al (2012) and Wang et al (2013Wang et al ( , 2015. From DIC applied to optical and environmental scanning electron microscope (ESEM) images, these authors showed how heterogeneous strain fields correlate with microstructure and recognised shear bands and tensile microcracks.…”
Section: Introductionmentioning
confidence: 99%
“…Claystones are sensitive to changes in hydric conditions that can lead to the shrinkage or the swelling of the clay matrix (Galle, 2001;Kang et al, 2003;Soe et al, 2007;GascBarbier and Tessier, 2007;Cosenza et al, 2007;Pineda et al, 2010;Hedan et al, 2012;Renard, 2012;Wang et al, 2013Wang et al, , 2015Desbois et al, 2014).…”
Section: Artefacts Caused By Drying and Unloadingmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, most traditional methods fail to image directly both the porosity down to the relevant pore scale and the preserved wet microstructure. Moreover, very few studies of mechanical behavior of clay (Urai and Wong, 1994;Wang et al, 2013Wang et al, , 2014 include microstructural observations, though microstructures could provide useful information about the deformation mechanisms. In clays, relevant scales for microstructural investigations range from hundreds of micrometers to just a few nanometers.…”
Section: Introductionmentioning
confidence: 99%